(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
One of the main elements of the suspension system is the lower control arm, which serves to transmit horizontal forces from the wheels to the chassis, while also defining the nature of the wheel movements relative to the chassis and the road surface. The implementation of guiding, elastic, and damping devices requires a comprehensive modelling of the vehicle's motion during the design stage. This paper presents results from static strength analysis and frequency analysis of the lower control arm of an independent front double-wishbone suspension of a passenger car. For this purpose, a three-dimensional geometric model of the lower control arm was created, using the Honda Civic as a prototype for the passenger car. The loads under various operating conditions necessary for conducting static analysis were determined. The Finite Element Analysis (FEA) was employed using the Simulation module of the SolidWorks software to solve the problem. Stresses, displacements, natural frequencies, and modes of the control arm were determined. The results were compared with experimentally obtained data for the natural frequencies.